2021
DOI: 10.4067/s0717-95022021000501480
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Model of the Ovine Stomach by Surface Scanning: Evaluation for Teaching Veterinary Anatomy

Abstract: This study investigated the use of fused deposition modeling (FDM), three-dimensional (3D) printed models, of the ovine stomach to learn surface and topographical anatomy. The objectives were: i) to faithfully reproduce the external morphology, the normal volume and the correct positioning of the four compartments of the stomach ii) to facilitate students the spatial visualization of the organ with emphasis on the complex relationship stomach-greater omentum. The model was built based on surface scanning. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…The printing machine was an Original Prusa i3 MK3S + 3D printer (PRUSA RESEARCH by JOSEF PRUSA, Czech). (25,29,54,47,53,55). The software and printer parameters are summarized in Table 1.…”
Section: Animalsmentioning
confidence: 99%
“…The printing machine was an Original Prusa i3 MK3S + 3D printer (PRUSA RESEARCH by JOSEF PRUSA, Czech). (25,29,54,47,53,55). The software and printer parameters are summarized in Table 1.…”
Section: Animalsmentioning
confidence: 99%
“…For example, using 3D‐printed models of an ovine stomach allowed students to gain a deeper understanding of the spatial structure of the stomach and its connection to the adjacent anatomical structure. This example represents a valuable and innovative teaching tool for the study of surface and topographical anatomy in veterinary medicine 18 . Furthermore, 3D scanning has been effectively used to generate skeletal models of the horse thoracic limb and bovine femur, which serve as valuable teaching aids for learning and practical application in the veterinary anatomy classes 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…This example represents a valuable and innovative teaching tool for the study of surface and topographical anatomy in veterinary medicine. 18 Furthermore, 3D scanning has been effectively used to generate skeletal models of the horse thoracic limb and bovine femur, which serve as valuable teaching aids for learning and practical application in the veterinary anatomy classes. 19,20 Understanding the complete topographical structure and spatial relationships of each bone in the head is more challenging compared to visceral organs and limb bones due to the presence of bone seam connections.…”
mentioning
confidence: 99%
“…They found no statistically significant difference between using 3D models and plastinated specimens for instruction considering the students' scores on a practical neuroanatomy exam [13]. Mendaza-DeCal and Rojo [14] developed a 3D printed model of an ovine stomach through a surface scanner for first year veterinary students to learn surface and topographical anatomy. They reported that the 3D printed ovine stomach model supported spatial visualization of anatomical relationships as a complement to a real stomach based on the students' assessments after studying both real and 3D printed model [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mendaza-DeCal and Rojo [14] developed a 3D printed model of an ovine stomach through a surface scanner for first year veterinary students to learn surface and topographical anatomy. They reported that the 3D printed ovine stomach model supported spatial visualization of anatomical relationships as a complement to a real stomach based on the students' assessments after studying both real and 3D printed model [14]. Assis Di Donato et al [15] created a didactic collection from 3D printed models of tongues from a cow, dog, horse, and pig for veterinary students to improve anatomy teaching together with existing cadaveric materials.…”
Section: Introductionmentioning
confidence: 99%